High quality oil recovery from oil-based drill cuttings via catalytic upgrading in presence of near-/supercritical water and different industrial wastes. (25th October 2021) - Chen, Zhong; Tong, Kun; He, Chunlan; Xue, Ming; Lyu, Chong; Chen, Hongzhen; Chen, Qiao; Xu, Yuanjian
Abstract: Near-/supercritical water (N/SCW) is a green and excellent medium for extracting and upgrading heavy oil from oil-based drill cuttings (OBDC). In order to improve the quality of recovered oil, five typical industrial wastes were adopted as the costless addictives, namely municipal sewage sludge (MSS), zinc-rich electroplating sludge (Zn-EPS), nickel-rich electroplating sludge (Ni-EPS), red mud (RM) and hot steaming steel slag (HSSS). The results indicate that the MSS deteriorates the recovered oil because the inferior bio-diesel was generated from the organics of MSS. The others exhibit positive effects more or less due to their dual functions of absorption and catalysis. The active components were found to be mainly metallic oxides in RM, ferrite in HSSS and metal hydroxides in EPS, respectively. Of which, the dehydration of metal hydroxides plays an important role in the N/SCW upgrading reactions, i.e., in-situ formation of high active compounds of ferrite and metallic oxides, and micro-mixing well with OBDC. In summary, the catalytic activity of tested industrial wastes was found to be in an order of Ni-EPS > Zn-EPS > HSSS > RM. High quality oil with zero asphaltene and extremely low heteroatom was obtained by N/SCW upgrading of OBDC with the addition of EPS. This study provides an alternative process for the sustainable and cleaner co-treatment of OBDC and various industrial wastes, and the obtained information is also helpful for the catalyst development of hydrothermal upgrading technology. Highlights: High quality oil was recovered from OBDC via hydrothermal catalytic upgrading. Five types of industrial wastes were adopted as the costless catalyst. Electroplating sludge shows the best catalytic activity. Dehydration of metal hydroxides in electroplating sludge is a key step.